A case report on weak subgroup of A: Aend - Saurabh Lahare; Ramesh Chandrakar; Minal Wasnik (Asian Journal of Transfusion Science)
A end is a weak subgroup of Blood group A, found rarely in general population, not detected by routine forward and reverse blood grouping, detected by Adsorption/Elution technique along with saliva testing for A, B and H antigens. Although it is subgroup of A but it lacks A antigen in saliva and contains only H antigen. A 25y/M was accepted for blood donation and showed weak/mf reaction with anti-A in forward grouping. On Adsorption/Elution testing eluate gave 2+ reaction with known A1 cells, and Saliva testing showed presence of only H substance. A weak A can be mistyped as O & can lead to a Hemolytic transfusion reaction so anti-H, anti-A1 & anti-AB should be incorporated in forward grouping and every O group sample should be treated with anti-AB antisera.